Public perception of smog: A case study in Ningbo City, China. (1st February 2017) - Yang, Shuncheng; Shi, Longyu
ABSTRACT: Smog has become a public environmental crisis in most areas of China, and in response, research efforts have mainly focused on the chemical properties of smog and its impact on human health. However, in-depth research on the public's perception of smog has not yet been conducted. A survey of residents living around eight state-controlled atmospheric environmental monitoring sites in Ningbo City was conducted using stratified sampling. The data was statistically analyzed to investigate people's views and behavioral tendencies in smog weather, the influence of different media reports on public outlook, and public opinions on the local atmosphere and pollution management in different areas. The results showed that people's perception of smog differs greatly from actual conditions, indicating that the public opinion tends to deviate when faced with a public crisis. Mainstream media (TV, newspaper, etc.), accounting for 67% of all media sources, are the main source for dissemination of smog information. The main sources of pollution, in order of decreasing contribution, according to residents of Ningbo City are as follows: motor vehicle exhaust, industrial coal combustion, large-scale construction, biomass burning, and kitchen fumes. Implications : Since 2011, most areas of China have been affected by frequent smog. Most research on smog has been concentrated on its causes, alert systems, and prevention measures, whereas in-depth research on the public perception of smog has not yet been conducted. When a risky environmental event such as smog occurs, consequences may be more serious than the event itself will cause if people take irrational measures because of lacking relevant knowledge. Therefore, investigating people's attitude and response to smog is both theoretically and practically significant.